2021
DOI: 10.5194/os-2021-83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using machine learning and beach cleanup data to explain litter quantities along the Dutch North Sea coast

Abstract: Abstract. Coastlines potentially harbor a large part of litter entering the oceans such as plastic waste. The relative importance of the physical processes that influence the beaching of litter is still relatively unknown. Here, we investigate the beaching of litter by analyzing a data set of litter gathered along the Dutch North Sea coast during extensive beach cleanup efforts between the years 2014–2019. This data set is unique in the sense that data is gathered consistently over various years by many volunt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Code and data availability. Code and data used to conduct the experiment and to create all of the figures are available at https: //doi.org/10.24416/UU01-QVIGJM (Ypma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Code and data availability. Code and data used to conduct the experiment and to create all of the figures are available at https: //doi.org/10.24416/UU01-QVIGJM (Ypma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although observations for the validation of this parameterization are limited, analysis by Pawlowicz et al (2019) of a set of beached drifters in the Salish Sea showed that this parameterization provides reasonable estimates for the beaching location. The choice for the beaching timescale, however, is uncertain and so far, values of λ B = 1-100 d have been used (e.g., Kaandorp et al, 2020Kaandorp et al, , 2022Onink et al, 2021). It seems that mainly quantitative analyses such as mass budgets are sensitive to the choice of the beaching timescale, but that beaching patterns are qualitatively robust against the choice for λ B .…”
Section: Beaching Parameterizationmentioning
confidence: 99%
See 3 more Smart Citations